O cangaço como ofício : uma análise da cultura profissional e da carreira no bando de Lampião - Souza, Felipe Trindade de (2020)
This dissertation investigates how some men from the Northeast of Brazil became cangaceiros, remained in an organized band and made cangaço an occupation. For this, we take Lampião's band as an empirical universe. Therefore, through this research it will be possible to understand the group of general knowledge of the group and describe how the transition from paisanos to cangaceiros occurred through a career. During the survey of discussions about the research field, we realized that the studies already carried out do not highlight socialization and the professional culture in the Lampião group. However, these elements constitute an outstanding role in the sociology of professional groups and deviation. Therefore we emphasize that in the process of entering individuals into a deviant group, professional socialization was configured as a means of initiation into a professional and self-building culture. In addition, the mastery of this complex of knowledge and attitudes allowed the cangaceiro to carry out the tasks in his dayto-day life in the band and eventually ascend to leadership positions. For this reason, in addition to several contingent episodes, such as death and imprisonment, cangaceiros who were unable to master this knowledge’s repertories tended not to solve the problems of the occupation and leave the band.